The Impact of Scratch Programming on Improving Students English Skills - Yayang Ariawan; Djoko Sutrisno (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study examines the influence of Scratch programming on enhancing students' proficiency in the English language. The research was carried out for a duration of two years in five primary schools. It employed a quantitative descriptive approach, gathering data using online surveys from a total of 18 instructors. The findings suggest that the use of Scratch programming has a substantial positive impact on different facets of English competence, such as the acquisition of vocabulary, comprehension of instructional material, reading and writing abilities, and grammar skills. Teachers expressed a strong understanding of Scratch and noticed significant enhancements in their pupils' linguistic skills. The results endorse the incorporation of visual programming languages such as Scratch into school curriculum as a means to successfully augment English language education. Additional research is advised to investigate the long-term effects and optimal methods for incorporating Scratch into language learning environments